Let's breathe again together in Antalya - SARAÇOĞLU, AYTEN (My University, 2022)
On behalf of the EAMS President, the Scientific Committee of the 6th European Airway Congress, and the Board of Directors of the European Airway Management Society, we would like to provide the readers of our journal and all other airway enthusiasts with further information about this important airway management event. The congress will be held at Pine Beach Belek Resort in Antalya, Turkey from the 28th of September till the 1st of October 2022 [1]. This conference will be organized under the motto: “Breathing again!“, which may fully describe the situation after more than two years of COVID-19 pandemics. The conference website at: https://www.eac2022.org is fully functional at the moment and provides detailed information about the venue, scientific program, abstract submission rules, accommodation, and social events associated with the conference. The congress is as usual preceded by the “Teach the airway teacher” course on Thursday, September 28th. The scientific program itself is balanced into theoretical lectures and hands-on sessions. Keynote lectures are devoted to the presentation of new guidelines such as PUMA (Project for Universal Management of Airways) [2] and ASA 2022 Guidelines [3], novel concepts of videolaryngoscopy, flow-regulated ventilation in the Intensive Care Unit, controlled ventilation with minimal or no device in the airway or recommendations how to teach airway management in the online era.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Anesteziyoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Anesthesiology; ANESTEZİYOLOJİ; Klinik Tıp; Klinik Tıp (MED); ANESTHESIOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine